Heterostructure growth, electrical transport and electronic structure of crystalline Dirac nodal arc semimetal PtSn4 - Edward L. Beynon; Oliver J. Barker; Tim D. Veal; Liam O’Brien; Marita O’Sullivan (Scientific Reports)
Abstract Topological semimetals have recently garnered widespread interest in the quantum materials research community due to their symmetry-protected surface states with dissipationless transport which have potential applications in next-generation low-power electronic devices. One such material, $$\hbox {PtSn}_{4}$$ , exhibits Dirac nodal arcs and although the topological properties of single crystals have been investigated, there have been no reports in crystalline thin film geometry. We examined the growth of $$\hbox {PtSn}_{4}$$ heterostructures on a range of single crystals by optimizing the electron beam evaporation of Pt and Sn and studied the effect of vacuum thermal annealing on phase and crystallinity. The electrical resistivity was fitted to a modified Bloch–Grüneisen model with a residual resistivity of 79.43(1) $$μ Ω$$ cm at 2K and a Debye temperature of 200K. Nonlinear Hall resistance indicated the presence of more than one carrier type with an effective carrier mobility of 33.6 $$\hbox {cm}^2\, \hbox {V}^{-1}\, \hbox {s}^{-1}$$ and concentration of 1.41 $$× 10^{21}\, \hbox {cm}^{-3}$$ at 300 K. X-ray photoemission spectra were in close agreement with convolved density of states and a work function of 4.7(2) eV was determined for the $$\hbox {PtSn}_{4}$$ (010) surface. This study will facilitate measurements that require heterostructure geometry, such as spin and topological Hall effect, and will facilitate potential device incorporation in future quantum technologies.